Development Economics as Taught in Developing Countries - Mckenzie, David; Paffhausen, Anna Luisa (World Bank, Washington, DC, 2016)
This paper uses a combination of survey questions to instructors and data collected from course syllabi and examinations to examine how the subject of development economics is taught at the undergraduate and masters levels in developing countries, and benchmark this against undergraduate classes in the United States. The study finds that there is considerable heterogeneity in what is considered development economics: there is a narrow core of only a small set of topics such as growth theory, poverty and inequality, human capital, and institutions taught in at least half the classes, with substantial variation in other topics covered. In developing countries, development economics is taught largely as a theoretical subject coupled with case studies, with few courses emphasizing data or empirical methods and findings. This approach contrasts with the approach taken in leading U.S. economics departments and with the evolution of development economics research. The analysis finds that country income per capita, the role of the state in the economy, the education level in the country, and the involvement of the instructor in research are associated with how close a course is to the frontier. The results suggest there are important gaps in how development economics is taught.